Dramatic Enhancement of Macrozoobenthic Species β-Diversity in Response to Artificial Breakwater Construction Along a Tropical Coastline - Huan Chiao Lee; Christopher J. Glasby; Anja Schulze; Han Raven; Siong Kiat Tan; Takaomi Arai; Amirah Md Jin; Nurun Nazihah Tal’ah; Ainina Zarifi; David J. Marshall (Diversity)
The beneficial or detrimental effects of human-built marine structures (piers, breakwaters, and seawalls) on macrozoobenthic assemblages and diversities are currently underexplored. The present study investigated the enhancement of β-diversity of oysterbed-associated species on breakwaters constructed along sandy beaches. We compared habitat complexities and species assemblages among artificial breakwater shores (ABS), a natural rocky shore (NS), and an embayment shore (ES). Oysterbed habitat complexity was found to be greatest on the ABS due to the successional colonization of the reef-forming estuarine oyster, Saccostrea echinata, followed by the colonization of boring bivalves and burrowing annelids. High-resolution taxonomic data revealed that the ABS supports the greatest species richness, including 48.1% unique species and 33.3% species shared with the embayment shore. The other shores uniquely or in combination with ABS support up to 11.1% of the total species richness associated with the oysterbeds (n = 81). Taxonomic dominance in terms of species number was Mollusca > Annelida > Arthropoda. This study reveals that ABS enhances β-diversity by ~91% (Jaccard dissimilarity index), which is driven by the sequential cascading events of (1) sheltering of shores, (2) colonization of novel habitat-forming oysters, (3) novel macrozoobenthic species recruitment from adjacent shores and sheltered embayments, including habitat-forming bivalves and annelids, and (4) the recruitment of macrozoobenthic species to boreholes. ABS habitat complexity derives from a spatially distinct, three-tiered ecological engineering system, involving (1) breakwater construction (100 m), (2) reef-forming oysters (10 m), and (3) boring bivalves and burrowing annelids (<10 cm). Irrespective of the purpose of their construction, breakwaters along extended sandy shores can potentially increase the resilience (β-diversity) and regional interconnectivity of hard surface macrozoobenthic species.